Binder for secondary battery electrode provided with secondary battery negative electrode containing silicon-based active material, and use thereof
By using an electrode adhesive containing a specific polymer, the problem of peeling the electrode mixture layer during charging and discharging of the secondary battery is solved, and the cycle characteristics and energy density of the battery are significantly improved.
Patent Information
- Application Number
- CN202380057922.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-08
- Filing Date
- 2023-07-31
- Publication Date
- 2025-04-15
AI Technical Summary
During the charging and discharging process, the electrode mixture layer is peeled off or shed due to the change in the volume of the silicon-based active substance during the charge and discharge process, resulting in a decrease in capacity and deterioration of the circulation characteristics.
By adjusting the molar ratio and structural unit ratio of the polymer and the strength of the adhesive coating film and the circulation characteristics of the secondary battery are improved by adjusting the molar ratio and structural unit ratio of the adhesive film.
It significantly improves the strength and toughness of the adhesive coating and the circulation characteristics of the secondary battery, extends the service life of the battery and increases the energy density.
Smart Images

Figure BDA0005261947840000281
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode binder for a negative electrode of a secondary battery containing a silicon-based active material and use thereof. Background Art
[0002] As secondary batteries, various power storage devices such as nickel-metal hydride secondary batteries, lithium-ion secondary batteries, and double-layer capacitors are put into practical use. These electrodes for secondary batteries are made by coating and drying the composition on the collector, wherein the composition is a composition for forming an electrode mixture layer containing an active material and an adhesive. For example, in lithium-ion secondary batteries, as an adhesive for a negative electrode mixture layer composition, an aqueous adhesive containing styrene butadiene rubber (SBR) latex and carboxymethyl cellulose (CMC) is used. On the other hand, as an adhesive for a positive electrode mixture layer, N-methyl-2-pyrrolidone (NMP) solution of polyvinylidene fluoride (PVDF) is widely used.
[0003] In recent years, with the expansion of the use of various secondary batteries, the demand for improving energy density, reliability and durability has tended to increase. For example, in order to increase the capacitance of lithium-ion secondary batteries, the use of silicon-based active materials as negative electrode active materials has increased. However, it is known that silicon-based active materials have a large volume change during charge and discharge, and the electrode mixture layer may peel off or fall off with repeated use, resulting in a problem of reduced battery capacity and deterioration of cycle characteristics (durability). In order to suppress such defects, studies have been conducted to improve durability by firmly bonding active materials with a binder (adhesiveness), reducing the size of active materials to alleviate stress associated with swelling and shrinkage, or studying additives to the electrolyte.
[0004] Among them, it is reported that acrylic polymers are effective as a binder having good cycle characteristics and achieving an effect of improving the durability of a negative electrode mixture layer using a silicon-based active material. Patent document 1 discloses a binder containing a cross-linked acrylic acid polymer cross-linked with polyacrylic acid by a specific cross-linking agent, and discloses that the electrode structure is not destroyed even when an active material containing a silicon-based active material is used, and good cycle characteristics are shown. Although the binder disclosed in Patent document 1 can provide good cycle characteristics, there is a tendency to increase the ratio of silicon-based active materials in order to improve the performance of secondary batteries, and a binder that can obtain higher cycle characteristics is needed.
[0005] As a binder for secondary battery electrodes that can improve the cycle characteristics of secondary batteries, for example, Patent Document 2 discloses a binder for non-aqueous electrolyte secondary battery electrodes, which includes a copolymer of vinyl alcohol and an alkali metal neutralized product of an olefinically unsaturated carboxylic acid, and at least one of poly(meth)acrylic acid and an alkali metal neutralized product of poly(meth)acrylic acid, and the embodiments specifically record that the binder has good bonding strength to the negative electrode active material, namely artificial graphite. Prior art literature Patent Literature
[0006] Patent Document 1: International Publication No. 2014 / 065407 Patent Document 2: International Publication No. 2019 / 065704 Summary of the invention Technical problem to be solved by the invention
[0007] However, Patent Document 2 does not contain any specific description of the battery characteristics of the secondary battery, and does not record the effectiveness in a system in which the active material contains a silicon-based active material at a high concentration, wherein the secondary battery is a secondary battery having a secondary battery negative electrode containing a silicon-based active material, and the silicon-based active material has a volume change of 2 to 4 times during charge and discharge.
[0008] The present invention is an invention completed in view of such a situation, and its purpose is to provide an electrode binder, the electrode binder can improve the toughness of the binder coating and the cycle characteristics of a secondary battery, the secondary battery is a secondary battery having a secondary battery negative electrode containing a silicon-based active material. In addition, a composition for a secondary battery negative electrode mixture layer containing the above-mentioned binder, a secondary battery negative electrode obtained using the composition, and a secondary battery are also provided. Technical means to solve technical problems
[0009] The inventors of the present invention have conducted in-depth research to solve the above-mentioned problems, and found that by using an electrode adhesive, the toughness of the adhesive coating and the cycle characteristics of the secondary battery are better, thereby completing the present invention, wherein the electrode adhesive contains a carboxyl-containing polymer or its salt, and a hydroxyl-containing polymer that may have a carboxyl group different from the polymer, and the secondary battery is a secondary battery having a secondary battery negative electrode containing a silicon-based active material.
[0010] The present invention is as follows. [1] An electrode binder, the electrode binder being an electrode binder for a secondary battery, the secondary battery having a secondary battery negative electrode containing a silicon-based active material, wherein the electrode binder contains a carboxyl group-containing polymer or a salt thereof (hereinafter referred to as "polymer (A)") and a hydroxyl group-containing polymer that may have a carboxyl group or a salt thereof (but different from "polymer (A)", hereinafter referred to as "polymer (B)"). [2] The electrode binder according to [1], wherein the number of moles of carboxyl groups in the polymer (A) (hereinafter referred to as “m A ”) and the molar number of hydroxyl groups possessed by the polymer (B) (hereinafter referred to as “m B ”) The Rc value calculated by the following formula (1) is 0.1 or more and 0.9 or less. Rc value = m A / (m A +m B ) (1) [3] The electrode binder according to [1] or [2], wherein the polymer (A) contains 40% by mass or more and 100% by mass or less of a structural unit derived from an ethylenically unsaturated carboxylic acid monomer based on all structural units thereof. [4] The binder for an electrode according to any one of [1] to [3], wherein the polymer (B) has a structural unit derived from vinyl alcohol. [5] The electrode binder according to any one of [1] to [4], wherein the polymer (B) has a carboxyl group or a salt thereof, and the molar ratio of the carboxyl group to the hydroxyl group is 5 / 95 or less. [6] A binder for an electrode, wherein the tensile product of a binder coating obtained from the binder for an electrode as described in any one of [1] to [5] is 50 or more as a value calculated by the following formula (2). Tensile product (MPa·%) = maximum stress (MPa) × elongation at break (%) (2). [7] The electrode binder according to any one of [1] to [6], wherein the content of the silicon-based active material is 30% by mass or more relative to the total amount of the active material. [8] A composition for a secondary battery negative electrode mixture layer, comprising the electrode binder according to any one of [1] to [7], a silicon-based active material, and water. [9] A secondary battery negative electrode, comprising a mixture layer formed from the composition for a secondary battery negative electrode mixture layer according to [8] on a surface of a current collector.
[10] A secondary battery comprising the secondary battery negative electrode according to [9]. Beneficial Effects
[0011] According to the binder for an electrode of the present invention, it is possible to improve the toughness of the binder coating film and the cycle characteristics of a secondary battery having a secondary battery negative electrode containing a silicon-based active material. In this regard, it is believed that: in the case of an adhesive containing only polymer (A), the strong hydrogen bonds between the carboxyl groups contained in polymer (A) make the mechanical properties of the coating film brittle. In contrast, in the case of an adhesive using a polymer (B) in combination, the carboxyl group forms a hydrogen bond with the hydroxyl group, which relaxes the hydrogen bonds between the carboxyl groups of the polymer (A), thereby obtaining strong toughness of the adhesive coating. DETAILED DESCRIPTION
[0012] The electrode binder of the present invention (hereinafter also referred to as "the present binder") contains the above-mentioned polymer (A) and the above-mentioned polymer (B), and can be made into a secondary battery negative electrode mixture layer composition (hereinafter also referred to as "the present composition") by mixing with a silicon-based active material and water. From the viewpoint of achieving the effect of the present invention, the above-mentioned composition is preferably an electrode slurry in a slurry state that can be applied to the collector, and can also be modulated into a wet powder state so that it can cope with stamping processing on the surface of the collector. The secondary battery negative electrode of the present invention can be obtained by forming a mixture layer formed by the above-mentioned composition on the surface of a collector such as copper foil.
[0013] Hereinafter, the polymer (A), the polymer (B), the present binder, the secondary battery negative electrode mixture layer composition obtained by using the present binder, the secondary battery electrode, and the secondary battery are described in detail, respectively. In the present specification, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid, "(meth)acrylate" means acrylate and / or methacrylate, and "(meth)acryloyl" means acryloyl and / or methacryloyl. In the numerical ranges recorded in stages in this specification, the upper limit value or lower limit value recorded in one numerical range may be replaced by the upper limit value or lower limit value of the numerical range recorded in other stages, and the upper limit value or lower limit value of the numerical range may also be replaced by the value shown in the embodiment.
[0014] 1. Polymer (A) The polymer (A) has a structural unit derived from an ethylenically unsaturated carboxylic acid monomer (hereinafter also referred to as "component (a)"), and a monomer component including the component (a) can be introduced into the polymer by performing known polymerization (solution polymerization, precipitation polymerization, suspension polymerization, emulsion polymerization, etc.). In addition, polymer (A) may be a cross-linked polymer or a non-cross-linked polymer. A cross-linked polymer and a non-cross-linked polymer may be used alone or in combination. In addition, a cross-linked polymer or a non-cross-linked polymer may be used alone or in combination of two or more.
[0015] <Structural Unit Derived from Ethylenically Unsaturated Carboxylic Acid Monomer> The polymer (A) has a carboxyl group by having a structural unit derived from the component (a), thereby improving the adhesion to the collector and having excellent lithium ion desolvation effect and ion conductivity, thereby obtaining an electrode with low resistance and excellent high-rate characteristics. In addition, since water-swellability is imparted, the dispersion stability of the silicon-based active material in the composition can be improved.
[0016] As the (a) component, for example, there can be mentioned (meth)acrylic acid, itaconic acid, crotonic acid, maleic acid, fumaric acid; (meth)acrylamide alkyl carboxylic acids such as (meth)acrylamide caproic acid and (meth)acrylamide dodecanoic acid; succinic acid monohydroxyethyl (meth)acrylate, ω-carboxy-caprolactone mono(meth)acrylate, β-carboxyethyl (meth)acrylate and other carboxyl-containing ethylenically unsaturated monomers or their (partial) alkaline neutralizations, one of which can be used alone or two or more can be used in combination. Among the above, from the viewpoint of obtaining a polymer with a long primary chain length (primary chain length) due to a fast polymerization rate and good bonding strength of the adhesive, a compound having an acryloyl group as a polymerizable functional group is preferred, and acrylic acid is particularly preferred. When acrylic acid is used as an ethylenically unsaturated carboxylic acid monomer, a polymer with a high carboxyl content can be obtained.
[0017] The content of component (a) in polymer (A) is not particularly limited, and preferably contains 40% by mass or more and 100% by mass or less relative to all structural units of polymer (A). By containing component (a) in the range, the negative electrode mixture layer of the secondary battery can be made tough. The lower limit can be, for example, 50.0% by mass or more, and, for example, 60.0% by mass or more, and, for example, 70.0% by mass or more. In addition, the upper limit is, for example, 96.0% by mass or less, and, for example, 90.0% by mass or less, and, for example, 80.0% by mass or less, and, for example, 70.0% by mass or less.
[0018] <Other structural units> In addition to the component (a), the polymer (A) may also contain other structural units derived from ethylenically unsaturated monomers that can be copolymerized with them (hereinafter also referred to as "component (b)"). As the component (b), for example, structural units derived from hydroxyl-containing ethylenically unsaturated monomers (monomers represented by the following formula (1) and monomers represented by the following formula (2)), ethylenically unsaturated monomer compounds having anionic groups other than carboxyl groups such as sulfonic acid groups and phosphoric acid groups, or nonionic ethylenically unsaturated monomers can be cited. These structural units can be introduced by copolymerizing monomers including ethylenically unsaturated monomer compounds having anionic groups other than carboxyl groups such as sulfonic acid groups and phosphoric acid groups, or nonionic ethylenically unsaturated monomers. CH2=C(R 1 )COOR 2 (1) [Where R 1 represents a hydrogen atom or a methyl group, R 2 represents a monovalent organic group having 1 to 8 carbon atoms and having a hydroxyl group, (R 3 O) m H or R 4 O[CO(CH2)5O] n H. In addition, R 3 represents an alkylene group having 2 to 4 carbon atoms, R 4 represents an alkylene group having 1 to 8 carbon atoms, m represents an integer of 2 to 15, and n represents an integer of 1 to 15.] CH2=C(R 5 )CONR 6 R 7 (2) [Where R 5 represents a hydrogen atom or a methyl group, R 6 represents a hydroxyl group or a hydroxyalkyl group having 1 to 8 carbon atoms, R 7 represents a hydrogen atom or a monovalent organic group.] The polymer (A) is different from the polymer (B) described below, and has a structural unit derived from the component (a) and a structural unit derived from the hydroxyl group-containing ethylenically unsaturated monomer polymer.
[0019] The proportion of component (b) can be 0.1% by mass or more and 20% by mass or less relative to the total structural units of the polymer (A). The proportion of component (b) can be 0.5% by mass or more and 17.5% by mass or less, 1.0% by mass or more and 15% by mass or less, 2% by mass or more and 12.5% by mass or less, or 3% by mass or more and 10% by mass or less. In addition, when the proportion of component (b) is 0.1% by mass or more relative to the total structural units of the polymer (A), the lithium ion conductivity can be expected to be improved due to the improved affinity for the electrolyte.
[0020] From the viewpoint of excellent cohesiveness of the binder containing the salt of the polymer (A), as component (b), hydroxyl-containing ethylenically unsaturated monomers are preferred among the above. In addition, from the viewpoint of obtaining an electrode with good bending resistance, structural units derived from nonionic ethylenically unsaturated monomers are preferred, and as nonionic ethylenically unsaturated monomers, (meth)acrylamide and its derivatives, nitrile-containing ethylenically unsaturated monomers, alicyclic structure-containing ethylenically unsaturated monomers, etc. can be cited.
[0021] The monomer represented by the above formula (1) is a (meth)acrylate compound having a hydroxyl group. 2 In the case of a monovalent organic group having 1 to 8 carbon atoms and having a hydroxyl group, the number of the hydroxyl group may be only one or may be two or more. The monovalent organic group is not particularly limited, and examples thereof include alkyl groups that may have a linear, branched, or cyclic structure, aryl groups, and alkoxyalkyl groups. 2 for (R 3 O) m H or R 4 O[CO(CH2)5O] n In the case of H, R 3 or R 4 The alkylene group represented may be a linear or branched chain.
[0022] Examples of the monomer represented by the formula (1) include hydroxyalkyl (meth)acrylates having a hydroxyalkyl group having 1 to 8 carbon atoms, such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, hydroxyhexyl (meth)acrylate, and hydroxyoctyl (meth)acrylate; polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polybutylene glycol mono(meth)acrylate, and polyethylene glycol mono(meth)acrylate. Polyalkylene glycol mono(meth)acrylates such as polypropylene glycol mono(meth)acrylate; dihydroxyalkyl(meth)acrylates such as glycerol mono(meth)acrylate; caprolactone-modified hydroxymethacrylate (manufactured by Daicel Corporation, trade names "Placcell FM1", "Placcell FM5", etc.), caprolactone-modified hydroxyacrylate (manufactured by Daicel Corporation, trade names "Placcell FA1", "Placcell FA10L", etc.), etc. Regarding the monomer represented by the above formula (1), one of them may be used alone, or two or more of them may be used in combination.
[0023] The monomer represented by the above formula (2) is a (meth)acrylamide derivative having a hydroxyl group or a hydroxyalkyl group having 1 to 8 carbon atoms. 7represents a hydrogen atom or a monovalent organic group. The monovalent organic group is not particularly limited, and examples thereof include alkyl groups that may have a linear, branched, or cyclic structure, aryl groups, and alkoxyalkyl groups, preferably organic groups having 1 to 8 carbon atoms. 7 It may be a hydroxyl group or a hydroxyalkyl group having 1 to 8 carbon atoms.
[0024] Examples of the monomer represented by the formula (2) include hydroxy(meth)acrylamide; (meth)acrylamide derivatives having a hydroxyalkyl group having 1 to 8 carbon atoms, such as N-hydroxyethyl(meth)acrylamide, N-hydroxypropyl(meth)acrylamide, N-hydroxybutyl(meth)acrylamide, N-hydroxyhexyl(meth)acrylamide, N-hydroxyoctyl(meth)acrylamide, N-methylhydroxyethyl(meth)acrylamide, and N-ethylhydroxyethyl(meth)acrylamide; and N,N-dihydroxyalkyl(meth)acrylamide, such as N,N-dihydroxyethyl(meth)acrylamide and N,N-dihydroxyethyl(meth)acrylamide. The monomer represented by the formula (2) may be used alone or in combination of two or more.
[0025] Examples of (meth)acrylamide derivatives include N-alkyl (meth)acrylamide compounds such as N-isopropyl (meth)acrylamide and N-tert-butyl (meth)acrylamide; N-alkoxyalkyl (meth)acrylamide compounds such as N-n-butoxymethyl (meth)acrylamide and N-isobutoxymethyl (meth)acrylamide; and N,N-dialkyl (meth)acrylamide compounds such as N,N-dimethyl (meth)acrylamide and N,N-diethyl (meth)acrylamide. Any one of these may be used alone or in combination of two or more.
[0026] As the ethylenically unsaturated monomer containing a nitrile group, for example, there can be mentioned: (meth) acrylonitrile; (meth) cyanoalkyl acrylate compounds such as (meth) cyanomethyl acrylate and (meth) cyanoethyl acrylate; cyano group-containing unsaturated aromatic compounds such as 4-cyanostyrene and 4-cyano-α-methylstyrene; 1,1-biscyanoethylene (シアンビニリデン); one of them can be used alone, or two or more can be used in combination. From the viewpoint of a large content of nitrile groups, acrylonitrile is preferred among the above.
[0027] Examples of the ethylenically unsaturated monomer containing an alicyclic structure include cycloalkyl (meth)acrylates which may have an aliphatic substituent such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, cyclodecyl (meth)acrylate, and cyclododecyl (meth)acrylate; isobornyl (meth)acrylate, adamantyl (meth)acrylate, cyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dipentylcyclo (meth)acrylate; and cycloalkyl polyol mono(meth)acrylates such as cyclohexanedimethanol mono(meth)acrylate and cyclodecane dimethanol mono(meth)acrylate. Any of these may be used alone or in combination of two or more.
[0028] From the viewpoint of excellent adhesiveness of the adhesive, the polymer (A) preferably contains structural units derived from the monomer represented by the above formula (1), the monomer represented by the above formula (2), (meth)acrylamide and its derivatives, and ethylenically unsaturated monomers containing a nitrile group, ethylenically unsaturated monomers containing an alicyclic structure, etc. From the viewpoint of excellent effect of improving the adhesiveness of the present adhesive, as the component (b), hydroxyalkyl (meth)acrylates having a hydroxyalkyl group having 1 to 8 carbon atoms are more preferred, and 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate are further preferred.
[0029] In addition, as component (b), when a structural unit from a hydrophobic ethylenically unsaturated monomer having a solubility of less than 1g / 100ml in water is introduced, a strong interaction with the electrode material can be achieved, and good adhesion to the silicon-based active material can be exerted. Thus, a strong and well-integrated negative electrode mixture layer can be obtained. Therefore, as the above-mentioned "hydrophobic ethylenically unsaturated monomer having a solubility of less than 1g / 100ml in water", an ethylenically unsaturated monomer containing an alicyclic structure is particularly preferred.
[0030] In addition, as other nonionic ethylenically unsaturated monomers, for example, (meth)acrylates can be used. Examples of (meth)acrylates include alkyl (meth)acrylate compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; Aromatic (meth)acrylate compounds such as phenyl (meth)acrylate, phenyl methyl (meth)acrylate, phenyl ethyl (meth)acrylate, and phenoxyethyl (meth)acrylate; Alkoxyalkyl (meth)acrylate compounds such as 2-methoxyethyl (meth)acrylate and 2-ethoxyethyl (meth)acrylate, etc.; these may be used alone or in combination of two or more.
[0031] From the viewpoint of adhesion to silicon-based active materials and cycle characteristics, aromatic (meth)acrylate compounds can be preferably used. From the viewpoint of further improving lithium ion conductivity and high rate characteristics, compounds having ether bonds are preferably used, and the compounds having ether bonds are (meth)acrylic acid alkoxyalkyl esters such as 2-methoxyethyl (meth)acrylate and 2-ethoxyethyl (meth)acrylate, and more preferably 2-methoxyethyl (meth)acrylate.
[0032] From the viewpoint of obtaining a polymer with a long primary chain length due to a fast polymerization rate and good adhesive strength of the adhesive, compounds having an acryloyl group are preferred among the nonionic ethylenically unsaturated monomers. In addition, from the viewpoint of good bending resistance of the obtained electrode, compounds having a homopolymer glass transition temperature (Tg) of 0°C or less are preferred as nonionic ethylenically unsaturated monomers.
[0033] The salt of polymer (A) is a salt in which part or all of the carboxyl groups contained in the polymer are neutralized. The type of salt is not particularly limited, and examples thereof include: alkali metal salts such as lithium salts, sodium salts and potassium salts; alkaline earth metal salts such as magnesium salts, calcium salts and barium salts; other metal salts such as aluminum salts; ammonium salts and organic amine salts. Among them, alkali metal salts and alkaline earth metal salts are preferred, and alkali metal salts are more preferred, from the viewpoint of not easily adversely affecting battery characteristics.
[0034] 1.1. When the polymer (A) is a cross-linked polymer The polymer (A) may be a polymer having a crosslinked structure (the present crosslinked polymer). The crosslinking method in the present crosslinked polymer is not particularly limited, and for example, the following method can be used. 1) Copolymerization of a crosslinking monomer (however, different from the above-mentioned multifunctional crosslinking agent) 2) Chain transfer to polymer chains during free radical polymerization The crosslinked polymer has a crosslinked structure, and thus, an adhesive containing the crosslinked polymer salt can have excellent adhesive strength. Among the above, the method of copolymerizing a crosslinkable monomer is preferred from the viewpoint of easy operation and easy control of the degree of crosslinking.
[0035] <Crosslinking Monomer> Examples of the crosslinkable monomer include a polyfunctional polymerizable monomer having two or more polymerizable unsaturated groups and a monomer having a self-crosslinkable crosslinkable functional group such as a hydrolyzable silyl group.
[0036] The above-mentioned multifunctional polymerizable monomer is a compound having two or more polymerizable functional groups in the molecule, wherein the polymerizable functional group is (meth) acryloyl, alkenyl, etc. The above-mentioned multifunctional polymerizable monomer can include multifunctional (meth) acryloyl compounds, multifunctional alkenyl compounds, compounds having both (meth) acryloyl and alkenyl, etc. With regard to these compounds, one kind can be used alone, or two or more kinds can be used in combination. Among them, from the viewpoint of easily obtaining a uniform cross-linked structure, a multifunctional alkenyl compound is preferred, and a multifunctional allyl ether compound having two or more allyl ether groups in the molecule is particularly preferred.
[0037] Examples of the polyfunctional (meth)acryloyl compound include di(meth)acrylates of diols such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate; poly(meth)acrylates such as tri(meth)acrylates and tetra(meth)acrylates of tri- or higher-valent polyols such as trimethylolpropane tri(meth)acrylate, trimethylolpropane ethylene oxide-modified tri(meth)acrylate, glycerol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate; and bisamides such as methylenebisacrylamide and hydroxyethylenebisacrylamide.
[0038] Examples of the polyfunctional alkenyl compound include polyfunctional allyl ether compounds such as trimethylolpropane diallyl ether, trimethylolpropane triallyl ether, pentaerythritol diallyl ether, pentaerythritol triallyl ether, tetraallyloxyethane, and polyallylsucrose; polyfunctional allyl compounds such as diallyl phthalate; and polyfunctional vinyl compounds such as divinylbenzene.
[0039] Examples of the compound having both a (meth)acryloyl group and an alkenyl group include allyl (meth)acrylate, isopropenyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, and 2-(2-vinyloxyethoxy)ethyl (meth)acrylate.
[0040] Specific examples of the monomer having a self-crosslinkable crosslinkable functional group include hydrolyzable silyl group-containing vinyl monomers, N-methoxyalkyl (meth) acrylamide, etc. These compounds may be used alone or in combination of two or more.
[0041] The vinyl monomer containing a hydrolyzable silyl group is not particularly limited as long as it is a vinyl monomer having at least one hydrolyzable silyl group. Examples thereof include: vinyl silanes such as vinyl trimethoxysilane, vinyl triethoxysilane, vinyl methyl dimethoxysilane, and vinyl dimethyl methoxysilane; silyl-containing acrylic acid esters such as trimethoxysilyl propyl acrylate, triethoxysilyl propyl acrylate, and methyl dimethoxysilyl propyl acrylate; silyl-containing methacrylic acid esters such as trimethoxysilyl propyl methacrylate, triethoxysilyl propyl methacrylate, methyl dimethoxysilyl propyl methacrylate, and dimethyl methoxysilyl propyl methacrylate; silyl-containing vinyl ethers such as trimethoxysilyl propyl vinyl ether; silyl-containing vinyl esters such as trimethoxysilyl undecanoic acid vinyl ester, and the like.
[0042] In the case where the cross-linked polymer is a polymer obtained by crosslinking a crosslinking monomer, relative to the total amount of 100 parts by mass of the monomer (non-crosslinking monomer) other than the crosslinking monomer, the usage amount of the crosslinking monomer is preferably 0.01 parts by mass or more and 5.0 parts by mass or less, more preferably 0.05 parts by mass or more and 3.0 parts by mass or less, more preferably 0.1 parts by mass or more and 2.0 parts by mass or less, further preferably 0.1 parts by mass or more and 1.7 parts by mass or less, and more preferably 0.5 parts by mass or more and 1.5 parts by mass or less. If the usage amount of the crosslinking monomer is more than 0.01 parts by mass, it is preferred from the viewpoint of better sedimentation stability of cohesiveness and electrode slurry. If it is less than 5.0 parts by mass, there is a tendency that the stability of precipitation polymerization or dispersion polymerization becomes higher.
[0043] For the same reason, the amount of the cross-linking monomer used is preferably 0.001 mol% to 2.5 mol%, more preferably 0.01 mol% to 2.0 mol%, further preferably 0.05 mol% to 1.75 mol%, further preferably 0.05 mol% to 1.5 mol%, and further preferably 0.1 mol% to 1.0 mol%, relative to the total amount of monomers other than the cross-linking monomer (non-cross-linking monomer).
[0044] (Regarding the characteristics of the present cross-linked polymer salt) Regarding the present cross-linked polymer, in the present composition, it is preferred to neutralize the acid groups such as carboxyl groups derived from the ethylenically unsaturated carboxylic acid monomers in a manner such that the neutralization degree is 20 mol% or more, and use it in the form of a salt. The above-mentioned neutralization degree is more preferably 50 mol% or more, further preferably 70 mol% or more, further preferably 75 mol% or more, further more preferably 80 mol% or more, and particularly preferably 85 mol% or more. The upper limit of the neutralization degree is 100 mol%, and may be 98 mol%, and may be 95 mol%. In the case where the neutralization degree is 20 mol% or more, it is preferred from the viewpoint of good water swelling and easy dispersion stabilization effect. In this specification, the above-mentioned neutralization degree can be calculated by calculating the feeding value of the monomer having an acid group such as a carboxyl group and the neutralizing agent used for neutralization. In addition, the cross-linked polymer salt can be subjected to IR measurement of the powder after drying at 80°C for 3 hours under reduced pressure conditions, and the neutralization degree can be confirmed by the intensity ratio of the peak of the C=O group derived from the carboxylic acid and the peak of the C=O group derived from the carboxylate.
[0045] <Particle Size of the Cross-linked Polymer Salt> In the present composition, the present crosslinked polymer salt is preferably present as water-swellable particles having an appropriate particle size, rather than being present as large-diameter aggregates (secondary aggregates), so that the adhesive containing the crosslinked polymer salt can exhibit good adhesive properties.
[0046] For the present cross-linked polymer, the particle size (water-swollen particle size) when a polymer having a neutralization degree of 80 mol% to 100 mol% based on the carboxyl group possessed by the cross-linked polymer is dispersed in water is preferably in the range of 0.1 μm to 10.0 μm in terms of volume-based median diameter. The more preferred range of the above particle size is 0.15 μm to 8.0 μm, the further preferred range is 0.20 μm to 6.0 μm, the further preferred range is 0.25 μm to 4.0 μm, and the further preferred range is 0.30 μm to 2.0 μm. If the particle size is in the range of 0.30 μm to 2.0 μm, it exists uniformly in the present composition with a suitable size, so the present composition has high stability and can exert excellent adhesion. If the particle size is greater than 10.0 μm, there is a risk that the adhesion becomes insufficient as described above. In addition, from the viewpoint of difficulty in obtaining a coating surface with smoothness, there is a risk that the coating property becomes insufficient. On the other hand, when the particle size is less than 0.1 μm, there is a concern from the viewpoint of stable manufacturability.
[0047] (Method for producing the present cross-linked polymer) The present polymer can be obtained by a method comprising the step of polymerizing a monomer component containing a monomer component containing an ethylenically unsaturated carboxylic acid monomer by precipitation polymerization or dispersion polymerization. Here, precipitation polymerization is a method of producing a polymer by performing a polymerization reaction in a solvent, wherein the solvent is a solvent that dissolves the monomer as a raw material but does not substantially dissolve the generated polymer. As the polymerization proceeds, the polymer particles grow larger by aggregation and growth, and a dispersion liquid is obtained in which primary particles of tens of nm to hundreds of nm are secondary aggregated into polymer particles of several μm to tens of μm. In order to control the particle size of the polymer, a dispersion stabilizer may also be used. In addition, the above-mentioned secondary aggregation can also be suppressed by selecting a dispersion stabilizer, a polymerization solvent, etc. Generally, precipitation polymerization in which secondary aggregation is suppressed is also called dispersion polymerization.
[0048] In the case of precipitation polymerization, the polymerization solvent may be selected from water and various organic solvents, etc., in consideration of the type of monomer used, etc. In order to obtain a polymer with a longer primary chain length, it is preferred to use a solvent with a small chain transfer constant.
[0049] As specific polymerization solvents, in addition to water-soluble solvents such as methanol, tert-butyl alcohol, acetone, methyl ethyl ketone, acetonitrile and tetrahydrofuran, benzene, ethyl acetate, ethylene dichloride, n-hexane, cyclohexane and n-heptane can also be cited, and one of them can be used alone or in combination of two or more. Alternatively, they can also be used as a mixed solvent with water. In the present invention, a water-soluble solvent means a solvent whose solubility in water at 20° C. is greater than 10 g / 100 ml. Among the above, methyl ethyl ketone and acetonitrile are preferred from the viewpoints of less generation of coarse particles and less adhesion to the reactor, good polymerization stability, less likelihood of secondary aggregation of precipitated polymer microparticles (or easy loosening in an aqueous medium even if secondary aggregation occurs), the ability to obtain a polymer having a small chain transfer constant and a large degree of polymerization (primary chain length), and easy handling during neutralization in the steps described later.
[0050] As polymerization initiator, known polymerization initiators such as azo compounds, organic peroxides, inorganic peroxides can be used, without particular limitation. The conditions of use can be adjusted by using known methods such as thermal initiation, redox initiation of reducing agents, UV initiation, etc., so as to reach appropriate free radical generation amount. In order to obtain a cross-linked polymer with a long primary chain length, it is preferred to set conditions within the scope allowed by the manufacturing time so that the free radical generation amount further decreases.
[0051] When the total amount of the monomer components used is set to 100 parts by mass, the preferred amount of the polymerization initiator used is, for example, 0.001 to 2 parts by mass, and for example, 0.005 to 1 part by mass, and for example, 0.01 to 0.1 parts by mass. If the amount of the polymerization initiator used is 0.001 parts by mass or more, the polymerization reaction can be stably carried out, and if it is 2 parts by mass or less, a polymer with a long primary chain length is easily obtained.
[0052] The polymerization temperature also depends on the type and concentration of the monomers used, and is preferably 0° C. to 100° C., and more preferably 20° C. to 80° C. The polymerization temperature may be fixed or may be varied during the polymerization reaction. In addition, the polymerization time is preferably 1 minute to 20 hours, and more preferably 1 hour to 10 hours.
[0053] 1.2. When the polymer (A) is a non-crosslinked polymer The polymer (A) may be a polymer having no crosslinking structure (the present non-crosslinked polymer), and the present non-crosslinked polymer contains a structural unit derived from an ethylenically unsaturated carboxylic acid monomer (the above-mentioned component (a)). The method for introducing the component (a) of the present non-crosslinked polymer may be the same as the method described for the component (a) of the present crosslinked polymer.
[0054] From the viewpoint of solubility in water, the content of the component (a) in the present non-crosslinked polymer is 50% by mass or more and 100% by mass or less, preferably 60% by mass or more and 100% by mass or less, more preferably 70% by mass or more and 100% by mass or less, and further preferably 80% by mass or more and 100% by mass or less, relative to all structural units of the present non-crosslinked polymer.
[0055] <Other structural units> The non-crosslinked polymer may contain, in addition to the component (a), other structural units derived from ethylenically unsaturated monomers copolymerizable with the component (the above-mentioned component (b)). The method for introducing the component (b) may be the same as the method described for the component (b) of the present cross-linked polymer.
[0056] The proportion of the component (b) relative to the total structural units of the non-crosslinked polymer may be 0% by mass or more and 50% by mass or less. The proportion of the component (b) may be 1% by mass or more and 50% by mass or less, 2% by mass or more and 50% by mass or less, 5% by mass or more and 50% by mass or less, or 10% by mass or more and 50% by mass or less.
[0057] The non-crosslinked polymer may be in the form of a salt in which part or all of the carboxyl groups contained in the polymer are neutralized. The type of salt is not particularly limited, and examples thereof include: alkali metal salts such as lithium, sodium, and potassium; alkaline earth metal salts such as magnesium salts, calcium salts, and barium salts; other metal salts such as aluminum salts; ammonium salts and organic amine salts. Among them, alkali metal salts and alkaline earth metal salts are preferred, and alkali metal salts are more preferred, from the viewpoint of not easily adversely affecting battery characteristics.
[0058] Regarding the present non-crosslinked polymer, in the present composition, it is preferred to neutralize the acid groups such as carboxyl groups derived from the ethylenically unsaturated carboxylic acid monomer in a manner such that the neutralization degree is 20 mol% or more, and use it in the form of a salt. The above-mentioned neutralization degree is more preferably 50 mol% or more, further preferably 70 mol% or more, further preferably 75 mol% or more, further more preferably 80 mol% or more, and particularly preferably 85 mol% or more. The upper limit of the neutralization degree is 100 mol%, can be 98 mol%, can be 95 mol%. In the case where the neutralization degree is 20 mol% or more, it is preferred from the viewpoint of easily ensuring solubility in water. In this specification, the above-mentioned neutralization degree can be calculated by calculating the feeding value of the monomer having an acid group such as a carboxyl group and the neutralizing agent used for neutralization. In addition, the crosslinked polymer or its salt can be subjected to IR measurement of the powder after drying treatment at 80°C for 3 hours under reduced pressure conditions, and the neutralization degree can be confirmed based on the intensity ratio of the peak of the C=O group from the carboxylic acid to the peak of the C=O group from the carboxylate.
[0059] The weight average molecular weight (Mw) of the non-crosslinked polymer is not particularly limited, and is preferably 5000 or more, more preferably 10000 or more, from the viewpoint of obtaining an electrode mixture layer with excellent adhesion. Mw can be 100000 or more, 500000 or more, or 1000000 or more. The upper limit of Mw is also not particularly limited, and from the viewpoint of the operation in the manufacture, for example, can be 10000000 or less, or 5000000 or less.
[0060] (Method for producing the non-crosslinked polymer) As a method for producing the present non-crosslinked polymer, a known polymerization method (solution polymerization, precipitation polymerization, suspension polymerization, emulsion polymerization, etc.) can be used, and it may be appropriately selected depending on the molecular weight, composition, and the like. As the polymerization initiator, known polymerization initiators such as azo compounds, organic peroxides, and inorganic peroxides can be used without particular limitation. The use conditions can be adjusted by using known methods such as thermal initiation, redox initiation with a reducing agent, and UV initiation to achieve an appropriate amount of free radical generation. Furthermore, for the purpose of adjusting the molecular weight, a known chain transfer agent may be used as necessary.
[0061] 2. Polymer (B) The polymer (B) is a hydroxyl-containing polymer that may have a carboxyl group or a salt thereof (but different from the polymer (A)), and is not particularly limited, and examples thereof include a polymer having a structural unit derived from the above-mentioned hydroxyl-containing ethylenically unsaturated monomer, a polymer having a structural unit derived from vinyl alcohol (hereinafter also referred to as "component (c)"), etc. As the polymer (B), from the viewpoint of excellent toughness of the adhesive coating and the ability to improve the cycle characteristics of the secondary battery, a polymer having component (c) is particularly preferred, wherein the secondary battery is a secondary battery having a secondary battery negative electrode containing a silicon-based active material. In addition, polymer (B) may be a cross-linked polymer or a non-cross-linked polymer. The cross-linked polymer and the non-cross-linked polymer may be used alone or in combination. In addition, the cross-linked polymer or the non-cross-linked polymer may be used alone or in combination of two or more.
[0062] <Structural unit derived from vinyl alcohol> The method for introducing component (c) may include a method of saponifying a polymer, wherein the polymer is a polymer obtained by using a known polymerization method (solution polymerization, precipitation polymerization, suspension polymerization, emulsion polymerization, etc.) on a monomer component containing a vinyl ester compound, and the vinyl ester compound is vinyl acetate, vinyl propionate, etc. As the vinyl ester compound, vinyl acetate is preferred from the viewpoints of easy availability of raw materials, easy progress of saponification reaction, etc. The vinyl ester compound may be used alone or in combination of two or more.
[0063] The proportion of the component (c) relative to all structural units of the polymer (B) may be 5% by mass or more and 100% by mass or less. The proportion of the component (c) may be 10% by mass or more and 100% by mass or less, 20% by mass or more and 100% by mass or less, 30% by mass or more and 100% by mass or less, 40% by mass or more and 100% by mass or less, or 50% by mass or more and 100% by mass or less.
[0064] <Other structural units> Furthermore, the polymer (B) may have a carboxyl group or a salt thereof. As a method for introducing the carboxyl group or a salt thereof, a method of saponifying the polymer may be cited, wherein the polymer is a polymer obtained by subjecting a monomer component containing a vinyl ester compound and an ethylenically unsaturated carboxylic acid ester compound to the above-mentioned known polymerization, the vinyl ester compound being vinyl acetate, vinyl propionate, etc., and the ethylenically unsaturated carboxylic acid ester compound being an alkyl (meth)acrylate compound, etc. Examples of the vinyl ester compound include vinyl acetate and vinyl propionate as described above, and vinyl acetate is preferred from the viewpoints of easy availability of raw materials and easy progress of saponification reaction. Examples of the alkyl (meth)acrylate compound include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, and the like. Methyl acrylate and methyl methacrylate are preferred because the saponification reaction is easy to proceed.
[0065] Here, in the case where the above-mentioned polymer (B) has a carboxyl group or a salt thereof, from the viewpoint of being able to improve the cycle characteristics of the secondary battery, the molar ratio of the carboxyl group to the above-mentioned hydroxyl group is preferably 5 / 95 or less, more preferably 4 / 96 or less, further preferably 3 / 97 or less, further preferably 2 / 98 or less, and further preferably 1 / 99 or less, wherein the secondary battery is a secondary battery having a secondary battery negative electrode containing a silicon-based active material. It is believed that in this case, the carboxyl group concentration of the above-mentioned polymer (B) is low, and after the dry composition is applied, the intermolecular interaction between the carboxyl groups and hydroxyl groups of other molecules becomes dominant compared to the simulated cyclic cross-linked structure within the molecule caused by the interaction between the carboxyl groups and hydroxyl groups in the same molecule, so that the adhesive coating is strengthened, thereby improving the cycle characteristics of the secondary battery, wherein the secondary battery is a secondary battery having a secondary battery negative electrode containing a silicon-based active material.
[0066] (Method for producing polymer (B)) As a method for producing the polymer (B), a known polymerization method (solution polymerization, precipitation polymerization, suspension polymerization, emulsion polymerization, etc.) can be used, and it may be appropriately selected depending on the molecular weight, composition, and the like. As the polymerization initiator, known polymerization initiators such as azo compounds, organic peroxides, and inorganic peroxides can be used without particular limitation. The use conditions can be adjusted by using known methods such as thermal initiation, redox initiation with a reducing agent, and UV initiation to achieve an appropriate amount of free radical generation. Furthermore, for the purpose of adjusting the molecular weight, a known chain transfer agent may be used as necessary.
[0067] When the polymer (B) has a carboxyl group, it may be in the form of a partially or completely neutralized salt. The type of salt is not particularly limited, and examples thereof include: alkali metal salts such as lithium, sodium, and potassium; alkaline earth metal salts such as magnesium salts, calcium salts, and barium salts; other metal salts such as aluminum salts; ammonium salts and organic amine salts. Among them, alkali metal salts and alkaline earth metal salts are preferred, and alkali metal salts are more preferred, from the viewpoint of not easily adversely affecting battery characteristics.
[0068] 3. This adhesive The present adhesive comprises a polymer (A) and a polymer (B). The amount of the polymer (A) and the polymer (B) used is preferably 0.05 based on the molar number (m) of the carboxyl group of the polymer (A) from the viewpoint of improving the toughness of the adhesive coating and the cycle characteristics of the secondary battery. A ) and the molar number (m B ) The Rc value calculated by the following formula (1) is preferably greater than 0.1 and less than 0.9, more preferably greater than 0.2 and less than 0.8, further preferably greater than 0.3 and less than 0.7, and even more preferably greater than 0.4 and less than 0.7, wherein the secondary battery is a secondary battery having a secondary battery negative electrode containing a silicon-based active material. Rc value = m A / (m A +m B ) (1)
[0069] In addition, the tensile product of the adhesive film obtained from the present adhesive is preferably 50 or more, more preferably 100 or more, further preferably 300 or more, further preferably 800 or more, and further preferably 1000 or more, from the viewpoint of being able to improve the cycle characteristics of the secondary battery, as calculated by the following formula (2), wherein the secondary battery is a secondary battery having a secondary battery negative electrode containing a silicon-based active material. In addition, the upper limit is not particularly limited, and 100000 MPa is the maximum value. Tensile product (MPa·%) = maximum stress (MPa) × elongation at break (%) (2)
[0070] 4. Composition for negative electrode mixture layer of secondary battery The secondary battery negative electrode mixture layer composition of the present invention contains the present binder, a silicon-based active material, and water. Relative to the total amount of 100 parts by mass of the silicon-based active material, the amount of the present adhesive in the present composition is, for example, 0.1 parts by mass or more and 20 parts by mass or less. The above-mentioned amount is also, for example, 0.2 parts by mass or more and 10 parts by mass or less, and is also, for example, 0.3 parts by mass or more and 8 parts by mass or less, and is also, for example, 0.4 parts by mass or more and 5 parts by mass or less. If the amount of the adhesive is 0.1 parts by mass or more, sufficient adhesion can be obtained. In addition, the dispersion stability of the silicon-based active material and the like can be ensured, and a uniform composite layer can be formed. If the amount of the adhesive is 20 parts by mass or less, the present composition will not become high viscosity, and the coating property to the collector can be ensured. As a result, a composite layer having a uniform and smooth surface can be formed.
[0071] As the silicon-based active material, an active material composed of silicon-based materials such as silicon, silicon alloys and silicon monoxide (SiO) can be used. With regard to its usage, from the viewpoint of being able to increase the capacitance of the lithium-ion secondary battery, it is preferred that the silicon-based active material contains 30% or more by mass in the total amount of active material, more preferably 35% or more by mass, further preferably 40% or more by mass, further preferably 45% or more by mass, and further preferably 50% or more by mass.
[0072] In addition, as the negative electrode active material, in addition to the silicon-based active material, it may also contain carbon-based materials, lithium metal, lithium alloys, and metal oxides, and one of them or a combination of two or more thereof may be used. Among them, the active material composed of carbon-based materials such as natural graphite, artificial graphite, hard carbon and soft carbon (hereinafter also referred to as "carbon-based active material") is preferred, and graphite such as natural graphite and artificial graphite, and hard carbon are more preferred. In addition, in the case of graphite, from the perspective of battery performance, spheroidized graphite is preferably used, and the preferred range of its particle size is, for example, 1 μm to 20 μm, and, for example, 5 μm to 15 μm. In addition, in order to improve the energy density, metals or metal oxides such as tin that can absorb lithium may also be used as negative electrode active materials. The carbon-based active material itself has good electrical conductivity, so it is not necessary to add a conductive aid. In the case of adding a conductive aid for the purpose of further reducing resistance, from the viewpoint of energy density, the amount used is, for example, 10 parts by mass or less, and, for example, 5 parts by mass or less relative to 100 parts by mass of the total amount of the active material.
[0073] When the present composition is in a slurry state, the amount of the active material used is, for example, in the range of 30% to 80% by mass, or, for example, in the range of 40% to 70% by mass, relative to the total amount of the present composition. If the amount of the active material used is 30% by mass or more, it is advantageous in terms of the drying cost of the medium while suppressing the migration of the adhesive, etc. On the other hand, if it is 80% by mass or less, the fluidity and coating properties of the present composition can be ensured, and a uniform mixture layer can be formed.
[0074] This composition uses water as a medium. In addition, for the purpose of adjusting the properties and dryness of this composition, a mixed solvent of a water-soluble organic solvent such as lower alcohols such as methanol and ethanol, carbonates such as ethylene carbonate, ketones such as acetone, tetrahydrofuran, N-methyl-2-pyrrolidone, etc. can be used. The proportion of water in the mixed medium is, for example, 50% by mass or more, and, for example, 70% by mass or more.
[0075] When the present composition is made into a coatable slurry, the content of the water-containing medium in the entire composition can be set to, for example, a range of 25% by mass to 60% by mass, and can be, for example, set to 35% by mass to 60% by mass, from the viewpoint of the coatability of the slurry, the energy cost required for drying, and productivity.
[0076] This composition can also be used in combination with other adhesive components such as styrene butadiene rubber (SBR) latex, carboxymethyl cellulose (CMC), acrylic latex and polyvinylidene fluoride latex. In the case of using other adhesive components, its usage amount can be set to, for example, 0.1 mass part to 5 mass parts or less relative to the total amount 100 mass parts of active material, in addition, for example, it can be set to 0.1 mass part to 2 mass parts or less, in addition, for example, it can be set to 0.1 mass part to 1 mass part or less. If the usage amount of other adhesive components is greater than 5 mass parts, the resistance increases, and there is a situation where high-rate characteristics are insufficient. From the viewpoint of excellent balance between cohesiveness and bending resistance, preferably SBR latex, CMC, more preferably SBR latex and CMC are used in combination.
[0077] The above-mentioned SBR latex refers to an aqueous dispersion of a copolymer having a structural unit derived from an aromatic vinyl monomer such as styrene and a structural unit derived from an aliphatic conjugated diene monomer such as 1,3-butadiene. As the above-mentioned aromatic vinyl monomer, in addition to styrene, α-methylstyrene, vinyltoluene, divinylbenzene, etc. can also be mentioned, and one or more of them can be used. Mainly from the viewpoint of adhesion, the structural unit derived from the above-mentioned aromatic vinyl monomer in the above-mentioned copolymer can be set to a range of, for example, 20% to 70% by mass, and can also be set to a range of, for example, 30% to 60% by mass. As the above-mentioned aliphatic conjugated diene monomer, for example, in addition to 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, etc. can also be cited, and one or more of them can be used. In terms of good adhesion of the binder and the flexibility of the obtained electrode, the structural unit derived from the above-mentioned aliphatic conjugated diene monomer in the above-mentioned copolymer can be set to a range of, for example, 30% to 70% by mass, and can also be set to a range of, for example, 40% to 60% by mass. In order to further improve the properties such as adhesion, in addition to the above-mentioned monomers, styrene / butadiene latex can also use the following monomers as other monomers and used as copolymer monomers: (meth) acrylonitrile and other nitrile-containing monomers; (meth) acrylic acid, itaconic acid, maleic acid and other carboxyl-containing monomers; (meth) methyl (meth) acrylate and other ester-containing monomers. The content of the structural unit derived from the other monomer in the copolymer can be, for example, in the range of 0% by mass to 30% by mass, and can also be, for example, in the range of 0% by mass to 20% by mass.
[0078] The above-mentioned CMC represents a nonionic cellulose-based semisynthetic polymer compound substituted with a carboxymethyl group and a salt thereof. Examples of the above-mentioned nonionic cellulose-based semisynthetic polymer compound include alkyl celluloses such as methyl cellulose, methylethyl cellulose, ethyl cellulose, and microcrystalline cellulose; hydroxyethyl cellulose, hydroxybutyl methyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose stearyl ether, carboxymethyl hydroxyethyl cellulose, alkyl hydroxyethyl cellulose, and nonylphenol polyether hydroxyethyl cellulose.
[0079] The composition for the negative electrode mixture layer of a secondary battery of the present invention has the above-mentioned binder, silicon-based active material and water as necessary constituents, and can be obtained by mixing the components using known means. There is no particular limitation on the mixing method of the components, and a known method can be used. It is preferred that the powder components such as active material, conductive aid and binder are dry-mixed and then mixed with a dispersion medium such as water for dispersion and kneading. In the case of obtaining the present composition in a slurry state, it is preferably processed into a slurry without poor dispersion and coagulation. As a mixing means, a planetary mixer, a thin film rotary mixer and a self-revolution mixer and other known mixers can be used. From the viewpoint of obtaining a good dispersion state in a short time, a thin film rotary mixer is preferably used. In addition, when a thin film rotary mixer is used, it is preferably pre-dispersed in a mixer such as a disperser (ディスパー). As long as the effect of the present invention is achieved, the pH of the above-mentioned slurry is not particularly limited, preferably less than 12.5, for example, in the case of cooperating with CMC, from the viewpoint of its small concern about hydrolysis, it is more preferably less than 11.5, and further preferably less than 10.5. In addition, as long as the effect of the present invention is achieved, the viscosity of the slurry is not particularly limited, and as a B-type viscosity (25° C.) at 20 rpm, it can be set to, for example, a range of 100 mPa·s to 6000 mPa·s, and further, for example, it can be set to 500 mPa·s to 5000 mPa·s, and further, for example, it can be set to a range of 1000 mPa·s to 4000 mPa·s. If the viscosity of the slurry is within the above range, good coating properties can be ensured.
[0080] 5. Secondary battery negative electrode The secondary battery negative electrode of the present invention is a negative electrode having a mixture layer formed by a composition for a secondary battery negative electrode mixture layer of the present invention on a current collector surface such as copper. The mixture layer can be formed by applying the composition on the surface of the current collector and then drying to remove water and other media. The method for applying the composition is not particularly limited, and known methods such as a doctor blade method, an immersion method, a roller coating method, a comma coating method, a curtain coating method, a gravure coating method, and an extrusion method can be used. In addition, the above-mentioned drying can be carried out by known methods such as warm wind blowing, decompression, (far) infrared rays, microwave irradiation, etc. Usually, the composite layer obtained after drying is subjected to compression treatment such as die stamping and roller pressing. By compressing the active material and the binder to be in close contact, the strength of the composite layer and the adhesion to the collector can be improved. By compression, for example, the thickness of the composite layer can be adjusted to about 30% to 80% of that before compression, and the thickness of the composite layer after compression is usually about 4 μm to 200 μm.
[0081] 6. Secondary batteries A secondary battery can be produced by providing the secondary battery negative electrode of the present invention with a secondary battery positive electrode, a separator, and an electrolyte solution. Here, as the positive electrode active material for the secondary electrode positive electrode, a lithium salt of a transition metal oxide can be used, for example, a layered rock salt type and a spinel type lithium-containing metal oxide can be used. Specific compounds of the layered rock salt type positive electrode active material include lithium cobalt oxide, lithium nickel oxide, and a so-called ternary system NCM {Li(Ni x ,Co y ,Mn z ), x+y+z=1} and NCA{Li(Ni 1-a-b Co a Al b )}, etc. In addition, as a spinel-type positive electrode active material, lithium manganate, etc. can be cited. In addition to oxides, phosphates, silicates and sulfur, etc. are also used; as phosphates, olivine-type lithium iron phosphate, etc. can be cited. As a positive electrode active material, one of the above can be used alone, or two or more can be combined as a mixture or a composite.
[0082] In addition, when the positive electrode active material containing a layered rock salt type lithium metal oxide is dispersed in water, the lithium ions on the surface of the active material are exchanged with the hydrogen ions in the water, and thus, the dispersion shows alkalinity. Therefore, there is a risk of corrosion of the common positive electrode collector material, i.e., aluminum foil (Al), etc. In such a case, it is preferred that the unneutralized or partially neutralized polymer is used as a binder to neutralize the alkali component dissolved from the active material. In addition, the amount of the unneutralized or partially neutralized polymer is preferably used in an amount of the unneutralized carboxyl group of the polymer relative to the alkali dissolved from the active material as an equivalent or more.
[0083] The electrical conductivity of the positive electrode active material is low, so a conductive aid is usually added for use. As a conductive aid, carbon materials such as carbon black, carbon nanotubes, carbon fibers, graphite powder, and carbon fibers (carbon fibers) can be cited, among which, from the viewpoint of easily obtaining excellent conductivity, carbon black, carbon nanotubes, and carbon fibers are preferably used. In addition, as carbon black, Ketjen black and acetylene black are preferably used. The conductive aid can be used alone or in combination with two or more of the above. From the viewpoint of taking into account both conductivity and energy density, the amount of the conductive aid used can be, for example, 0.2 to 20 parts by mass relative to the total amount of 100 parts by mass of the active material, and, for example, can be set to 0.2 to 10 parts by mass. In addition, the positive electrode active material can use a material coated with a conductive carbon material.
[0084] The electrolyte can be in liquid or gel form. The separator is arranged between the positive electrode and the negative electrode of the battery, and is responsible for preventing the short circuit caused by the contact between the two electrodes, maintaining the electrolyte and ensuring the ionic conductivity. For the separator, it is preferred to have a film-like insulating microporous film with good ion permeability and mechanical strength. As specific raw materials, polyolefins such as polyethylene and polypropylene, polytetrafluoroethylene, etc. can be used.
[0085] Regarding the electrolyte, commonly used known electrolytes can be used according to the type of active material. In lithium-ion secondary batteries, specific solvents include: cyclic carbonates with high dielectric constants and high electrolyte solubility such as propylene carbonate and ethylene carbonate; and low-viscosity chain carbonates such as ethyl methyl carbonate, dimethyl carbonate and diethyl carbonate; they can be used alone or as a mixed solvent. Lithium salts such as LiPF6, LiSbF6, LiBF4, LiClO4, and LiAlO4 are dissolved in these solvents and used as electrolytes. In nickel-hydrogen secondary batteries, potassium hydroxide aqueous solution can be used as an electrolyte. A secondary battery can be obtained by making the positive plate and the negative plate separated by a diaphragm into a rolled or stacked structure and storing them in a shell, etc.
[0086] The electrode binder disclosed in this specification has excellent toughness of the binder coating film, and a secondary battery having a secondary battery negative electrode obtained using the binder can ensure good integrity and show good durability (cycle characteristics) even after repeated charge and discharge, so it is suitable for automotive secondary batteries and the like. Example
[0087] The present invention will be described in detail below based on examples. The present invention is not limited to these examples. In addition, the following "parts" and "%" refer to parts by mass and mass % unless otherwise specified.
[0088] 《Manufacturing of carboxyl-containing polymer salts》 (Production Example 1: Production of Carboxyl Group-Containing Crosslinked Polymer Salt P-1) In the polymerization, a reactor equipped with a stirring blade, a thermometer, a reflux cooler, and a nitrogen inlet pipe was used. 875.6 parts of acetonitrile, 4.40 parts of ion exchange water, 100 parts of acrylic acid and 0.5 parts of pentaerythritol triallyl ether (manufactured by Osaka Soda Co., Ltd., trade name "Neoaryl P-30") were added to the reactor. After the reactor was fully purged with nitrogen, it was heated to raise the internal temperature to 55°C. After confirming that the internal temperature was stable at 55°C, 0.04 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Fujifilm and Kou Junyao Co., Ltd., trade name "V-65") as a polymerization initiator was added. As a result, white turbidity was confirmed in the reaction liquid, so this point was taken as the polymerization start point. The external temperature (water bath temperature) was adjusted, and the polymerization reaction was continued while the internal temperature was maintained at 55° C. The reaction solution was cooled after 5 hours from the polymerization start point. After the internal temperature dropped to 25° C., 52.5 parts of lithium hydroxide·monohydrate (hereinafter referred to as "LiOH·H2O") powder was added. After the addition, stirring was continued at room temperature for 12 hours to obtain a slurry-like polymerization reaction solution in which particles of the carboxyl-containing cross-linked polymer salt P-1 (Li salt, neutralization degree 90 mol%) were dispersed in the medium.
[0089] The obtained polymerization reaction liquid is centrifuged to precipitate the polymer and remove the supernatant. After that, the washing operation of redispersing the precipitate in acetonitrile of the same weight as the polymerization reaction liquid and then centrifuging the polymer particles to precipitate and remove the supernatant is repeated twice. The precipitate is recovered and the volatile components are removed by drying at 80°C for 3 hours under reduced pressure to obtain a powder of the carboxyl-containing cross-linked polymer salt P-1. The carboxyl-containing cross-linked polymer salt P-1 is hygroscopic and therefore sealed and stored in a container with water vapor barrier properties. In addition, the powder of the carboxyl-containing cross-linked polymer salt R-1 is subjected to IR measurement, and the degree of neutralization is calculated from the intensity ratio of the peak of the C=O group from the carboxylic acid to the peak of the C=O group from the lithium carboxylate. The result is equal to the calculated value based on the feed, which is 90 mol%.
[0090] 《Manufacturing of hydroxyl-containing polymers》 (Production Example 2: Production of Hydroxyl-Containing Polymer CP-1) In the polymerization, a reactor equipped with a stirring blade, a thermometer, a reflux cooler, and a nitrogen inlet pipe was used. 1 part of methyl acrylate (hereinafter referred to as "MA") and 19 parts of vinyl acetate (hereinafter referred to as "VAc") were mixed, and 0.67 parts of dimethyl 2,2'-azobis(isobutyrate) (manufactured by Fujifilm Wako Junyao Co., Ltd., trade name "V-601") was dissolved to prepare a monomer solution. 410 parts of water, 10 parts of anhydrous sodium sulfate, 1 part of partially saponified polyvinyl alcohol (manufactured by Kuraray Co., Ltd., trade name "PVA-217", saponification degree 88%), and 20.67 parts of the above-mentioned monomer solution were added to the reactor. After the reactor was fully purged with nitrogen, it was heated to raise the internal temperature to 60°C. After confirming that the internal temperature was stable at 60°C, a mixed solution of 4 parts of MA and 76 parts of VAc was dripped through a dropping funnel over 4 hours. After 1 hour from the completion of the dripping, the reaction solution was cooled to terminate the reaction, thereby obtaining a polymerization reaction solution containing a copolymer of MA and VAc. Here, the amount of the residual monomers was measured by gas chromatography (GC) and the polymerization rate of the monomers was calculated. The polymerization rate of each monomer was 98% for MA and 96% for VAc. In addition, after a part of the obtained polymerization reaction liquid was dissolved in tetrahydrofuran, it was filtered through a membrane filter (manufactured by ADVANTEC: pore size 0.45 μm), and the copolymer of MA and VAc was measured by gel permeation chromatography (GPC) under the following conditions. The weight average molecular weight (Mw) obtained by polystyrene conversion was 1.08 million. ○Measurement conditions Column: TSKgel SuperMultiporeHZ-M manufactured by Tosoh × 4 Solvent: Tetrahydrofuran Temperature: 40℃ Detector: RI Flow rate: 600 μL / min
[0091] After the polymerization reaction liquid containing the copolymer of MA and VAc was heated to an external temperature of 50°C, the solvent was removed under reduced pressure to remove the residual monomers. Thereafter, 500 parts of methanol and 38.8 parts of LiOH·H2O were added to 100 parts of the total amount of the comonomers (MA and VAc) charged, and a saponification reaction was carried out at an external temperature of 50°C for 3 hours to obtain a reaction liquid containing a saponified product of the copolymer of MA and VAc. The reaction solution containing the saponified product was reprecipitated in acetone, filtered, and then dried at 80° C. for 12 hours to remove volatile components, thereby obtaining a saponified product of a copolymer of MA and VAc (hereinafter also referred to as “hydroxyl-containing polymer CP-1”). Here, based on the polymerization ratio of MA and VAc, the hydroxyl-containing polymer CP-1 is a lithium salt of a hydroxyl-containing polymer having “7% by mass (4.7 mol%) of structural units derived from acrylic acid” and “93% by mass (95.3 mol%) of structural units derived from vinyl alcohol”. The hydroxyl-containing polymer CP-1 is hygroscopic and therefore is sealed and stored in a container having water vapor barrier properties. In addition, the powder of the hydroxyl-containing polymer CP-1 was subjected to IR measurement, and the neutralization degree was calculated from the intensity ratio of the peak of the C=O group derived from the carboxylic acid and the peak of the C=O derived from the carboxylic acid Li, and the result was 90 mol%.
[0092] (Production Example 3: Production of Hydroxyl-Containing Polymer CP-2) The same operation as in Production Example 2 was performed except that a monomer solution was prepared with 7.6 parts of MA and 12.4 parts of VAc and a mixed solution of 30.4 parts of MA and 49.6 parts of VAc was added dropwise through a dropping funnel over 4 hours. The polymerization ratios of the monomers were 95% for MA and 87% for VAc. Saponification was performed in the same manner as in Production Example 2 to obtain a saponified product of a copolymer of MA and VAc (hereinafter also referred to as "hydroxyl-containing polymer CP-2"). Here, based on the polymerization ratio of MA and VAc, hydroxyl-containing polymer CP-2 is a lithium salt of a hydroxyl-containing polymer having "51% by mass (40.1 mol%) of structural units derived from acrylic acid" and "49% by mass (59.9 mol%) of structural units derived from vinyl alcohol". The hydroxyl-containing polymer CP-2 is hygroscopic and therefore was sealed and stored in a container having water vapor barrier properties. In addition, the powder of the hydroxyl-containing polymer CP-2 was subjected to IR measurement, and the neutralization degree was calculated from the intensity ratio of the peak of the C=O group derived from the carboxylic acid and the peak of the C=O derived from the carboxylic acid Li, and the result was 90 mol%.
[0093] Example 1 (Production of Adhesive Coating Film) An aqueous solution (an 8% aqueous solution prepared by adding ion-exchanged water to carboxyl-containing cross-linked polymer salt P-1 as polymer (A) and polyvinyl alcohol PVA-1 (manufactured by Kuraray Co., Ltd., Kuraray Polyval 28-98 (degree of saponification 98 mol%), degree of polymerization 1700) as polymer (B)) was added into a container in the number of parts listed in Table 1, and then mixed at 2200 rpm for 7 minutes using a rotation-revolution mixer device (Shinki Corporation, Bubble Tori Rentaro ARE-310) to obtain an aqueous dispersion of a binder. Thereafter, the adhesive aqueous solution was poured into a tray, dried at 40° C. for 20 hours, and further vacuum dried at 80° C. for 12 hours. The adhesive coating obtained after drying was punched out into a size of a No. 8 dumbbell (JIS K6251) to prepare a test piece, and the toughness was measured.
[0094] Here, the Rc value is calculated as follows. Rc value = m A / (m A +m B ) m A : The number of moles of carboxyl groups in the polymer (A) m B : The number of moles of hydroxyl groups in polymer (B) ·m A =((the solid content of P-1: 9 parts)×(mass % of the structural unit derived from acrylic acid: 100%) / 100) / ((the molecular weight of the structural unit derived from acrylic acid: 72.06)×(1-(neutralization degree of P-1: 90 mol%) / 100)+(the molecular weight of the structural unit derived from lithium acrylate: 78.00)×(neutralization degree of P-1: 90 mol%) / 100))=0.12 ·m B =((solid content of PVA-1: 11 parts)×(mass % of structural unit derived from vinyl acetate: 100%) / 100) / ((molecular weight of structural unit derived from vinyl acetate: 86.09)×(1-(saponification degree of PVA-1: 98 mol%) / 100)+(molecular weight of structural unit derived from vinyl alcohol: 44.05)×(saponification degree of PVA-1: 98 mol%) / 100))=0.25 From this, it is calculated that the Rc value = 0.12 / (0.12+0.25) = 0.32.
[0095] (Toughness of adhesive coating) The test piece punched out from the adhesive coating was subjected to a tensile test at a speed of 7.5 mm / min using a tensile tester (Tensilon RTC-1210A manufactured by Orientec Corp.) The results showed a maximum stress of 62 MPa, a breaking elongation of 1.2%, and a Young's modulus of 5.1 GPa. In addition, the tensile product was calculated according to the following formula as an index of strength and toughness. Tensile product (MPa·%) = maximum stress (MPa) × elongation at break (%)
[0096] Example 2 to Example 7 and Comparative Example 1 to Comparative Example 5 The same operation as in Example 1 was carried out except that the compounding ratio was set as described in Table 1 to produce an adhesive coating film, and the toughness was evaluated. The results are shown in Table 1. In addition, the Rc value was calculated in the same manner as in Example 1. In addition, regarding Comparative Examples 1 and 5, since no adhesive coating film was obtained and the tensile test measurement could not be performed, they are described as “unable to measure” in Table 1.
[0097] [Table 1]
[0098] The details of the compounds used in Table 1 are shown below. P-2: polyacrylic acid (manufactured by Sigma Airdrich Co., Ltd., polyacrylic acid aqueous solution (solid content concentration 35% by mass), weight average molecular weight 100,000) P-3: sodium polyacrylate (manufactured by Toagosei Co., Ltd., sodium polyacrylate aqueous solution (solid content concentration 43% by mass), Alon (registered trademark) A-20L, weight average molecular weight 1,000,000) PVA-1: Polyvinyl alcohol (manufactured by Kuraray Co., Ltd., Kuraray Polyval 28-98 (saponification degree 98 mol%), degree of polymerization 1700) ·PVA-2: Polyvinyl alcohol (manufactured by Kuraray Co., Ltd., Kuraray Polyval 60-98 (saponification degree 98 mol%), degree of polymerization 2400) PVA-3: polyvinyl alcohol (manufactured by Nippon Acid Bio-Poval Co., Ltd., JL-18E (saponification degree 83 mol% to 86 mol%), degree of polymerization 1500)
[0099] Example 1 (Preparation of Negative Electrode Mixture Layer Composition 1) As active materials, graphite (trade name "SCMG-CF" manufactured by Showa Denko Co., Ltd.) and Si-based active materials (SiO 5 μm manufactured by Osaka Chitanium Technologies Co., Ltd.) were used. Acetylene black (Li400 manufactured by Denka Co., Ltd.) was used as a conductive additive. As a binder, a mixture of a carboxyl-containing crosslinked polymer salt P-1 as a polymer (A) and a hydroxyl-containing polymer PVA-1 as a polymer (B) was used. In a planetary mixer (Hibismics 2P-03 manufactured by Plurimics Corporation), ion exchange water was used as a diluent, and graphite: Si-based active material: acetylene black: binder (P-1 / PVA-1=9 / 11; Rc value 0.32) was added in a mass ratio of 30 / 45 / 5 / 20 (solid content) so that the solid content concentration of the negative electrode mixture layer composition became 37% by mass. The mixture was mixed for 1 hour and 30 minutes to prepare a slurry-state negative electrode mixture layer composition 1.
[0100] (Preparation of Negative Electrode Mixture Layer Composition 2) A negative electrode mixture layer composition 2 in a slurry state was prepared in the same manner as the negative electrode mixture layer composition 1 except that the mass ratio of graphite: Si-based active material: acetylene black: binder (P-1 / PVA-1=9 / 11; Rc value 0.32) was 50 / 25 / 5 / 20 (solid content).
[0101] (Manufacturing of Negative Electrode Plate 1) Next, the negative electrode mixture layer composition 1 was applied to a collector (copper foil) having a thickness of 16.5 μm using a variable coater, and dried in a ventilation dryer at 80°C for 15 minutes to form a mixture layer. After that, rolling was performed to make the mixture layer thickness 43 μm and the mixture density 2.30 ± 0.10 g / cm 3 Then, it was punched into 3 cm square to obtain the negative electrode plate 1.
[0102] (Manufacturing of Negative Electrode Plate 2) In addition to using negative electrode mixture layer composition 2, the mixture layer thickness was set to 30 μm and the mixture density was set to 1.60 ± 0.10 g / cm 3 The negative electrode plate 2 was obtained by performing the same adjustments as the negative electrode plate 1 except for the above.
[0103] (Production of positive electrode plate) LiNi as the positive electrode active material was mixed and added to N-methylpyrrolidone (NMP) solvent. 0.5 Co 0.2 Mn 0.3100 parts of O2 (NCM), 2 parts of acetylene black, and 4 parts of polyvinylidene fluoride (PVDF) as a positive electrode binder were mixed to prepare a positive electrode composite layer composition. The positive electrode composite layer composition was applied and dried on an aluminum current collector (thickness: 20 μm) to form a composite layer. After that, the composite layer was rolled to a thickness of 125 μm and a composite density of 3.0 g / cm 3 Then, it was punched into 3 cm squares to obtain the positive electrode plate.
[0104] (Preparation of Electrolyte) 1 mass % of vinylene carbonate (VC) and 2 mass % of fluoroethylene carbonate (FEC) were added to a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio EC:DMC=3:7), and LiPF6 was dissolved at 1.2 mol / L to prepare a non-aqueous electrolyte.
[0105] (Manufacturing of Secondary Batteries) The structure of the battery is as follows: lead terminals are installed on the positive and negative electrodes respectively, and the electrode bodies facing each other through a diaphragm (made of polyethylene: film thickness 16μm, porosity 47%) are placed in a material using an aluminum laminate as the battery outer body for liquid injection, and then sealed as a test battery. In addition, the design capacity of this trial battery is 50mAh. As the design capacity of the battery, it is designed based on the charge termination voltage of 4.2V. In addition, secondary batteries each including the negative electrode plate 1 and the negative electrode plate 2 as a negative electrode were produced.
[0106] <Evaluation of Cycle Characteristics> The laminated lithium ion secondary battery prepared above was charged and discharged at a charge and discharge rate of 0.1C under the condition of 2.5V to 4.2V by CC discharge at 45°C, and the initial capacity C0 was measured. Furthermore, the capacity C after 100 cycles was measured by repeatedly charging and discharging at a charge and discharge rate of 0.5C under the condition of 2.5V to 4.2V by CC discharge at 25°C. 100 . Here, the cycle characteristic (ΔC) is obtained by the following formula. ΔC=C 100 / C0×100(%) ΔC calculated from the above formula was 86.4%, and the cycle characteristics based on the following criteria were evaluated as "A". In addition, a higher ΔC value indicates better cycle characteristics. (Cycle Characteristics Criteria) A: The charge and discharge capacity retention rate is above 86.0% B: The charge and discharge capacity retention rate is 85.0% or more and less than 86.0% C: The charge and discharge capacity retention rate is 84.0% or more and less than 85.0% D: Charge and discharge capacity retention rate is less than 83.0%
[0107] Example 2 to Example 7 and Comparative Example 1 to Comparative Example 5 Except that the compounding ratio was set as described in Table 1, the same operation as in Example 1 was performed to prepare the negative electrode mixture layer composition 1 and the negative electrode mixture layer composition 2, respectively, and the cycle characteristics of the secondary batteries having the negative electrode plate 1 and the negative electrode plate 2 obtained using the compositions were evaluated. The results are shown in Table 1.
[0108] 《Evaluation Results》 It can be seen from the results of Examples 1 to 7 that the electrode adhesive of the present invention has excellent toughness of the adhesive coating and excellent cycle characteristics of the secondary battery, wherein the secondary battery has a secondary battery negative electrode obtained from a composition for a secondary battery negative electrode mixture layer, and the composition for a secondary battery negative electrode mixture layer contains the electrode adhesive of the present invention and a silicon-based active material. If the tensile product of these adhesive coatings is taken into consideration, when the tensile product is greater than 50 (Examples 1 to 7), the cycle characteristics of the secondary battery are good (C evaluation or above). In particular, when the tensile product is greater than 300 (Examples 2, 4 to 7), the cycle characteristics of the secondary battery are excellent results (B evaluation or above). Furthermore, when the tensile product is greater than 800 (Examples 4 to 6), the cycle characteristics of the secondary battery are even more excellent results (A evaluation).
[0109] Here, even in the case of using an electrode binder containing a polymer (A) and a hydroxyl-containing polymer CP-1 as a polymer (B) (the hydroxyl-containing polymer CP-1 is a hydroxyl-containing polymer CP-1 "copolymer of vinyl alcohol and an alkali metal neutralized product of an olefinically unsaturated carboxylic acid (carboxyl / hydroxyl = 4.7 / 95.3 (molar ratio))" having carboxyl groups and hydroxyl groups in the same molecule) (Example 3), the cycle characteristics of the secondary battery are evaluated as C. In this regard, it is believed that: the carboxyl concentration in CP-1 is low (<5 mol%), and after the dry composition is applied, the intermolecular interaction between the carboxyl groups and hydroxyl groups of other molecules becomes dominant compared to the simulated cyclic cross-linked structure within the molecule caused by the interaction between the carboxyl groups and hydroxyl groups in the same molecule, thereby strengthening the adhesive coating.
[0110] In contrast, when using an electrode binder containing no polymer (B) and containing polymer (A) (Comparative Examples 1 and 2), the toughness of the binder coating is poor and the cycle characteristics are also poor (D evaluation). In addition, for Comparative Example 1, the binder coating is brittle and cannot be subjected to a tensile test.
[0111] In addition, when an electrode binder containing no polymer (A) and polyvinyl alcohol as polymer (B) was used (Comparative Example 3), although the tensile product was 2530 MPa, showing high toughness, the cycle characteristics were significantly poor (D evaluation). This is believed to be because the foaming property of polyvinyl alcohol caused a plurality of tiny gaps to form in the negative electrode mixture layer, and further, compared with polymer (A), a stable SEI (Solid Electrolyte Interphase) was not formed on the surface of the silicon-based active material, and the silicon-based active material was micronized as it shrank during expansion and contraction during charge and discharge.
[0112] Furthermore, in the case of using an electrode binder containing no polymer (A) and containing a hydroxyl-containing polymer CP-1 as polymer (B) (the hydroxyl-containing polymer CP-1 is a hydroxyl-containing polymer CP-1 "copolymer of vinyl alcohol and alkali metal neutralization of olefinically unsaturated carboxylic acid (carboxyl group / hydroxyl group = 4.7 / 95.3 (molar ratio))" having carboxyl groups and hydroxyl groups in the same molecule) (Comparative Example 4), the tensile product is 560, showing high toughness, but the cycle characteristics are significantly poor (D evaluation). In this regard, it is believed that the foaming property of CP-1 causes multiple tiny gaps in the negative electrode mixture layer.
[0113] Furthermore, in the case of using an electrode adhesive that does not contain polymer (A) but contains a hydroxyl-containing polymer CP-2 as polymer (B) (the hydroxyl-containing polymer CP-2 is a hydroxyl-containing polymer CP-2 "copolymer of vinyl alcohol and alkali metal neutralization of olefinically unsaturated carboxylic acid (carboxyl / hydroxyl = 40.1 / 59.9 (molar ratio))" having carboxyl groups and hydroxyl groups in the same molecule) (Comparative Example 5), the adhesive coating is brittle and cannot be subjected to tensile test measurement, and the cycle characteristics of the secondary battery are also poor (D evaluation). This is believed to be because: in the case of using an electrode adhesive that does not contain polymer (A) but contains a hydroxyl-containing polymer CP-2 as polymer (B), water is removed after drying, resulting in the preferential generation of a simulated cyclic cross-linked structure within the molecule caused by the interaction between the carboxyl groups and hydroxyl groups in the same molecule, thereby increasing the rigidity of the main chain, that is, reducing the entanglement of the polymer chain, and thus reducing the toughness of the adhesive coating, making it unable to follow the expansion and contraction of the silicon-based active material. Industrial Applicability
[0114] Regarding the electrode adhesive of the present invention, while the adhesive coating has excellent toughness, a secondary battery having a secondary battery negative electrode obtained using an electrode slurry containing the adhesive and a silicon-based active material can ensure good integrity and show good durability (cycle characteristics) even after repeated charge and discharge, and is therefore expected to contribute to the high capacity of automotive secondary batteries, etc. The electrode binder of the present invention is particularly suitable for non-aqueous electrolyte secondary battery electrodes, and is particularly useful for non-aqueous electrolyte lithium ion secondary batteries having high energy density.
Claims
1. An electrode binder, the electrode binder is an electrode binder for a secondary battery, the secondary battery has a secondary battery negative electrode containing a silicon-based active material, wherein: The electrode binder contains a carboxyl group-containing polymer or a salt thereof (hereinafter referred to as "polymer (A)") and a hydroxyl group-containing polymer which may have a carboxyl group or a salt thereof (but is different from the "polymer (A)", hereinafter referred to as "polymer (B)").
2. The electrode binder according to claim 1, wherein Based on the molar number of carboxyl groups possessed by the polymer (A) (hereinafter referred to as "m A ”) and the molar number of hydroxyl groups possessed by the polymer (B) (hereinafter referred to as “m B ”), the Rc value calculated by the following formula (1) is 0.1 or more and 0.9 or less, Rc value = m A / (m A +m B ) (1).
3. The electrode binder according to claim 1 or 2, wherein The polymer (A) contains 40% by mass or more and 100% by mass or less of a structural unit derived from an ethylenically unsaturated carboxylic acid monomer based on all structural units thereof.
4. The electrode binder according to claim 1 or 2, wherein The polymer (B) has a structural unit derived from vinyl alcohol.
5. The electrode binder according to claim 1 or 2, wherein The polymer (B) has a carboxyl group or a salt thereof, and the molar ratio of the carboxyl group to the hydroxyl group is 5 / 95 or less.
6. An electrode binder, wherein: The tensile product of the binder coating obtained from the binder for an electrode according to claim 1 or 2 is 50 or more as a value calculated by the following formula (2), Tensile product (MPa·%) = maximum stress (MPa) × elongation at break (%) (2).
7. The electrode binder according to claim 1 or 2, wherein The content of the silicon-based active material is 30% by mass or more relative to the total amount of the active material.
8. A composition for a secondary battery negative electrode mixture layer, wherein: The composition for a secondary battery negative electrode mixture layer contains the electrode binder according to claim 1 or 2, a silicon-based active material, and water.
9. A secondary battery negative electrode, wherein: The secondary battery negative electrode comprises a mixture layer formed from the composition for a secondary battery negative electrode mixture layer according to claim 8 on a surface of a current collector.
10. A secondary battery, wherein: The secondary battery comprises the secondary battery negative electrode according to claim 9 .
Citation Information
Patent Citations
Binder for lithium cell, composition for producing electrode, and electrode
WO2014065407A1
Binder for nonaqueous electrolyte secondary battery electrode, electrode mixture for nonaqueous electrolyte secondary battery, electrode for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery, and electric apparatus
WO2019065704A1